Effects of Three Trans Isomers of Eicosapentaenoic Acid on Rat Platelet Aggregation and Arachidonic Acid Metabolism - Loï, C.; Chardigny, J. M.; Berdeaux, O.; Vatèle, J. M.; Poullain, D.; Noël, J. P.; Sébédio, J. L. (Thrombosis and Haemostasis, 1998)
Three trans isomers of eicosapentaenoic acid (EPA) were added to rat platelets stimulated with arachidonic acid (AA) in order to compare their effects on platelet aggregation and on AA oxygenation with those of EPA. The production of metabolites from radiolabelled 20:5Δ17trans was studied also.EPA induced an inhibition of platelet aggregation of 26.7 ± 6,6 % for a 20:5/20:4 ratio equal to 1. The 20:5Δ11trans and the 20:5Δ11trans,17trans were twice as antiaggregant. In contrast, the 20:5Δ17trans induced similar antiaggregant effect as its cis homologue. Each fatty acid showed a dose-dependent effect. In opposition to EPA, 20:5Δ17trans was also able to induce platelet aggregation (12 ± 4.9% at 5 μM). With regards to the metabolism of AA, 20:5Δ11trans, 20:5Δ17trans and 20:5Δ11trans,17trans (20:5/20:4 = 1) reduced the formation of the cyclooxygenase metabolites (-63%, -37% and -68%, respectively) and enhanced that of 12-HETE (+67%, +38% and +74%, respectively) as compared to EPA.The analysis showed that radiolabelled 20:5Δ17trans was metabolized into five compounds which remained to be identified. The Rf of three of these compounds (X1, X2 and X4) were those of the metabolites of EPA. Experiments using baicalein induced an inhibition of the production of X2. This suggested that this compound was formed through the 12-lipoxygenase pathway. In the same way, using indomethacin as inhibitor, we observed that X1 and X4 were produced by the cyclooxygenase pathway.Our results suggest that the trans double bond in the Δ11 position may be responsible of the different physiological effects of the trans polyunsaturated fatty acids as compared to their cis homologue (EPA). Furthermore, 20:5Δ17trans seems to be recognised by the enzymatic system as 20:4 n-6.